Digital–Turāth Convergence in Islamic Boarding School Education: Integrative Innovation Management for Digital Transformation and Curriculum Reform in the Era of Educational Disruption - Badrul Mudarris; Abdul Haq AS (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2026)
The rapid expansion of digital technologies has created significant challenges for traditional educational institutions, particularly Islamic boarding schools (pesantren), which are required to adapt to technological change while preserving their religious and cultural identity. This study aims to examine how integrative innovation management facilitates digital transformation and curriculum reform within a pesantren context. A qualitative explanatory case study was conducted at Nurul Jadid Islamic Boarding School, Probolinggo, Indonesia, between December 2025 and February 2026. Data were collected through participant observation, semi-structured interviews, document analysis, and institutional documentation involving institutional leaders, administrators, curriculum developers, teachers, information technology personnel, and students. The data were analyzed using Creswell’s thematic analysis framework through coding, categorization, theme development, and interpretation. The findings reveal five interconnected dimensions of integrative innovation management: (1) the orchestration of dynamic capabilities through charismatic-transformational leadership, (2) epistemological convergence between classical Islamic scholarship and digital literacy, (3) the development of a techno-pedagogical ecosystem that supports adaptive learning, (4) organizational resilience through open innovation management and strategic collaboration, and (5) the synthesis of dual competencies integrating technological proficiency and spiritual intelligence. These findings demonstrate that digital transformation in pesantren is not merely a technological process but a multidimensional institutional transformation grounded in religious values and organizational adaptability. The study contributes to educational management literature by proposing the Digital–Turāth Convergence framework, which explains how faith-based educational institutions can integrate technological innovation with traditional knowledge systems while maintaining their cultural and spiritual identity. The findings also provide practical insights for policymakers and educational leaders seeking sustainable models of curriculum reform and digital transformation in religious educational institutions.